Bio-efficacy of bio-rationals against citrus leaf miner (Phyllocnistis citrella) in acid lime (Citrus aurantiifolia) - N T, DILEEP KUMAR; A P, BIRADAR (The Indian Journal of Agricultural Sciences, 2024)
The field experiment was conducted during winter (rabi) 2020–21 and rainy (kharif) season of 2021–22 at College of Agriculture (University of Agricultural Sciences, Dharwad), Vijayapura, Karnataka to evaluate efficacy of bio-rationals against citrus leaf miner (Phyllocnistis citrella Stainton). The experiment was conducted in a randomized block design (RBD) with 8 treatments, viz. bio digester solution (10%); pongamia leaf extract (5%); Prosopis juliflora leaf extract (5%); Beauveria bassiana (2 × 108 conidia/g) (1 kg/ha); Bacillus thuringiensis 8 L (1 L/ha); neem-based insecticide (10000 ppm) (1.5 L/ha); thiamethoxam 25 wg (125 ml/ha) (standard check); and untreated control (water spray), replicated thrice. Among the selected bio-rationals, two application of neem (Azadirachta indica)-based insecticide recorded significantly lesser number of live mines/shoot followed by bio-digester solution (10%) and these treatments were found superior in controlling citrus leaf miner on acid lime [Citrus aurantiifolia (Christm.) Swingle]. The pongamia leaf extract, Bacillus thuringiensis 8 L and Beauveria bassiana were proved to be moderately affective against this pest. The bio-rationals found effective can be used in integrated management of citrus leaf miner on acid lime.